Coaching, talent identification and talent development in Para sport: Developing the field - Townsend, R.; Clare, O.; Maw, G. (Talent development in Paralympic sport: Researcher and practitioner perspectives, 2022)
This chapter provides an overview of the role of the coach in talent identification and development environments in Para sport. While interest in Para sport continues to grow, particularly in coaching, we know very little about the role, function and practices of coaching in talent identification and development in Para programmes. In this chapter we carefully examine coaching and talent identification through a disability lens, highlighting how coaches are implicated in `access work`, and questioning how coaches reconcile cultural understandings of disability with sport-specific conceptions of `talent`. In so doing we draw connections between coaching and disability studies, questioning the extent to which ableism may influence talent identification. Furthermore, we discuss coach and athlete development, illustrating the limits of `normative` models of athlete development applied to Para sport and the implications for coach education and development. Finally, we outline some key considerations for researchers and outline some productive lines of inquiry to develop the field.